2021
DOI: 10.3390/ijms22020591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Anti-Apoptotic SOD2 and BIRC3 in Periodontal Cells and Tissues

Abstract: The aim of the study was to clarify whether orthodontic forces and periodontitis interact with respect to the anti-apoptotic molecules superoxide dismutase 2 (SOD2) and baculoviral IAP repeat-containing protein 3 (BIRC3). SOD2, BIRC3, and the apoptotic markers caspases 3 (CASP3) and 9 (CASP9) were analyzed in gingiva from periodontally healthy and periodontitis subjects by real-time PCR and immunohistochemistry. SOD2 and BIRC3 were also studied in gingiva from rats with experimental periodontitis and/or orthod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Previous studies by our research group have shown that mechanical/orthodontic forces can regulate the bacteria-induced levels of some proinflammatory and anti-apoptotic molecules [17][18][19]. The synthesis of some of these molecules during periodontal inflammation is further enhanced by mechanical/orthodontic forces, whereas other molecules tend to be downregulated [17][18][19]. Overall, these studies show that mechanical/orthodontic forces can influence the host immunoinflammatory response to periodontal bacteria.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Previous studies by our research group have shown that mechanical/orthodontic forces can regulate the bacteria-induced levels of some proinflammatory and anti-apoptotic molecules [17][18][19]. The synthesis of some of these molecules during periodontal inflammation is further enhanced by mechanical/orthodontic forces, whereas other molecules tend to be downregulated [17][18][19]. Overall, these studies show that mechanical/orthodontic forces can influence the host immunoinflammatory response to periodontal bacteria.…”
Section: Introductionsupporting
confidence: 61%
“…The animal and in vitro experiments further showed that mechanical or orthodontic forces affect the bacteria-induced levels of such molecules very differently. For example, mechanical forces inhibited the stimulatory effect of F. nucleatum on CXCL1, CCL2, CCL5, SOD2, and BIRC3, whereas the F. nucleatum-induced upregulation of CXCL5, CXCL8, and CXCL10 was enhanced [17][18][19]. Overall, these previous studies demonstrated that mechanical/orthodontic forces can influence the host immunoinflammatory response to periodontal bacteria.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations